Application Requiring Management Engineering of Teaching in University of Najran According to the Staff View - Ali, Hanan Ibrahim Mohammed (Journal of Educational and Psychological Sciences, 2020)
This study aimed to the recognition of the reality and possibility of engineering management techniques university according to the staff point's of view.The sample were (180) staff members (90) of them were males and (85) were females. The tool used for gathering data is questionnaire contains of (32) section with 8 parts for every field and the four fields are prepared by the researcher The study followed the descriptive analytical method. The data obtained were lobulated and analyzed through (SPSS) programmer. The findings sum up that The highest average arithmetic for proposed field is 4.000 with a high degree of applicability , and the lowest average arithmetic for problems and difficulties is 3.000 with an average of applicability.
Keywords: Engineering Management; Requirements; Najran University Staff